(untitled) (Jurnal Anestesi Perioperatif, 2025)
Background: Propofol is widely used for induction of general anesthesia; however, it frequently associated hypotension due to vasodilation and myocardial depression. Vasopressors such as phenylephrine and ephedrine are commonly administered to counteract this effect, but evidence comparing their hemodynamic efficacy during induction remains limited. Methods: This randomized double-blind clinical trial included 80 patients undergoing elective surgery under general anesthesia. Patients were randomly allocated into two groups to receive either phenylephrine 100 µg or ephedrine 5 mg at the time of propofol induction. Demographic characteristics (sex, age, body mass index, and ASA physical status) were recorded. Hemodynamic parameters, including systolic blood pressure, diastolic blood pressure, mean arterial pressure, and heart rate, were measured after premedication and 30 seconds following propofol administration. Results: Baseline characteristics were comparable between the two groups. At 30 seconds after induction, there were no statistically significant differences in systolic blood pressure, diastolic blood pressure, mean arterial pressure, or heart rate between the phenylephrine and ephedrine groups. Both vasopressors effectively maintained hemodynamic stability during propofol induction. Discussion: The findings suggest that phenylephrine and ephedrine have similar hemodynamic profiles when administered during propofol induction. Despite their differing pharmacological mechanisms, both agents were equally effective in preventing early hypotension without significant differences in heart rate or blood pressure responses. Conclusion: Phenylephrine 100 µg and ephedrine 5 mg demonstrated comparable efficacy in maintaining hemodynamic stability during propofol-induced general anesthesia, with no significant difference in their ability to prevent hypotension.